Akt inhibitor MK‐2206 in combination with bendamustine and rituximab in relapsed or refractory chronic lymphocytic leukemia: Results from the N1087 alliance study. Issue 8 (1st June 2017) - Larsen, Jeremy T.; Shanafelt, Tait D.; Leis, Jose F.; LaPlant, Betsy; Call, Tim; Pettinger, Adam; Hanson, Curtis; Erlichman, Charles; Habermann, Thomas Matthew; Reeder, Craig; Nikcevich, Daniel; Bowen, Deborah; et al.
Abstract : Akt is a downstream target of B cell receptor signaling and is a central regulator of CLL cell survival. We aim to investigate the safety and efficacy of the Akt inhibitor MK‐2206 in combination with bendamustine and rituximab (BR) in relapsed and/or refractory CLL in a phase I/II study. A standard phase I design was used with cohorts of three plus three patients to determine the maximum tolerated dose (MTD) of MK‐2206 in combination with BR in relapsed CLL. Single‐agent MK‐2206 (weekly dosed) was administered one‐week in advance before BR on cycle 1 and subsequently was given with BR at the same time for cycle 2‐6. Phase II employed the MTD of MK‐2206 with BR to evaluate safety and efficacy of this study combination. Thirteen relapsed/refractory CLL were treated for maximal 6‐cycle of therapy. The maximum tolerated dose of MK‐2206 was 90 mg by mouth once weekly. The most common grade 3/4 adverse events were neutropenia (46%), febrile neutropenia (23%), rash (15%), diarrhea (15%), and thrombocytopenia (15%). Overall response rate was 92% with a median progression free survival and treatment free survival of 16 and 24 months, respectively. Five patients (38%) achieved complete remission or complete remission with incomplete count recovery, two of whom were MRD negative. The efficacy and tolerability of this combination indicates that Akt inhibition combined with chemoimmunotherapy is a promising novel treatment combination in CLL and deserves further prospective clinical trial.